Description of Tanytarsus binduensis sp. nov. and T. tamakutibasi Sasa (Diptera: Chironomidae) from India with their phylogenetic placement - Mondal, Arabinda; Hui, Poulami; Hazra, Niladri (Zootaxa, 2026)
A new species, Tanytarsus binduensis of the ‘triangularis’ species group of the genus Tanytarsus van der Wulp, 1874 is described based on the adult males from the Himalaya Biodiversity Hotspot, West Bengal, India. This is the first record of this species group from the Oriental region. We also present a redescription of Tanytarsus tamakutibasi Sasa, 1983, along with its COI barcode, first record of this species from India. A world keys to the known adult males of both species groups are also provided. Based on known adult males, a tentative cladistic relationship and a molecular phylogeny using available COI sequences of all species of the ‘triangularis’ and ‘tamakutibasi’ species groups are also provided. The newly described species Tanytarsus binduensis (‘triangularis’ group) exhibits a minimum interspecific distance of 14.82% with Tanytarsus aboensis (‘triangularis’ group) (AM398774).